Demand-driven energy supply from stored biowaste for biomethanisation. (October 2015) - Aichinger, Peter; Kuprian, Martin; Probst, Maraike; Insam, Heribert; Ebner, Christian
Highlights: Biowaste storage supported substrate hydrolysis leading to higher biomethane yields. Storage led to biowaste acidification and accumulation of volatile fatty acids. Fast methane production: >95% was produced within the first days. Abstract: Energy supply is a global hot topic. The social and political pressure forces a higher percentage of energy supplied by renewable resources. The production of renewable energy in form of biomethane can be increased by co-substrates such as municipal biowaste. However, a demand-driven energy production or its storage needs optimisation, the option to store the substrate with its inherent energy is investigated in this study. The calorific content of biowaste was found unchanged after 45 d of storage (19.9 ± 0.19 kJ g −1 total solids), and the methane yield obtained from stored biowaste was comparable to fresh biowaste or even higher (approx. 400 m 3  Mg −1 volatile solids). Our results show that the storage supports the hydrolysis of the co-substrate via acidification and production of volatile fatty acids. The data indicate that storage of biowaste is an efficient way to produce bioenergy on demand. This could in strengthen the role of biomethane plants for electricity supply the future.